Integrasi nilai-nilai kejujuran dan keadilan sebagai pilar utama dalam upaya pemberantasan korupsi menurut analisis Al-qur’an dan Hadits - Setyo, Mohammad Amri; Karisma, Nisaul; Alam, Ahmad Haikal Surya; Nurimama, Sifa Taqiya; Tofara, Alzida; Tsalats, Muafiqo (Maliki Interdisciplinary Journal, 2025)
This study aims to integrate the values of honesty and justice as the main foundations in combating corruption. The objective is to explore the concepts and analyze anti-corruption efforts based on the perspectives of the Qur’an and Hadith. This research employs a qualitative research method and a thematic interpretation approach (Maudui) to examine verses from the Qur’an and Hadith related to the values of honesty (Al-Sidq), justice (Al-‘Adl), and the prohibition of corrupt practices. The results indicate that the Qur’an and Hadith strongly emphasize the importance of internalizing honesty and justice in all aspects of life, including financial management and public trust. In Islam, honesty is seen not only as a moral attitude but also as an expression of faith and devotion to Allah SWT. Justice is viewed as a fundamental principle that must be adhered to in community and national life. The integration of these two values establishes an effective value system that can prevent and eliminate corrupt practices. This study also shows that the application of integrity and justice must be supported by a strong monitoring system and strict sanctions in line with sharia principles. In conclusion, combating corruption requires a comprehensive approach that combines spiritual, moral, and organizational aspects based on integrity and justice, as taught in the Qur’an and Hadith.